DARE Newsletter, Vol. 6, No. 1, Winter 2003 - DARE; Berns, Roland L.; Simon, David (Dictionary of American Regional English, 2003)
Contents: "A Scientific Portrait" by Roland L. Berns; "Funding Update" by David Simon; "Notes and Quotes"; "Contributors to DARE in 2002"; "Staff Member Profile: Kate Peterson"; "DARE Editor Wins Award: Luanne von Schneidemesser"; "Celebrating Volume IV"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States